Solution to sustainable rural electrification in Myanmar. (June 2016) - Pode, Ramchandra; Pode, Gayatri; Diouf, Boucar
Abstract: About 70% population of Myanmar lives in rural areas where average electrification rate is mere 16%. Out of total 64, 917 villages, about 57, 557 villages are in remote areas, far away from the national grid. Myanmar is blessed with an abundance of energy potential and extensive renewable resources, including large amount of agricultural biomass waste. The rice husk is one of the major sources of biomass. The paddy rice production had been estimated at 28.9 million tons for 2014, producing 5.78 million tons of rice husks. Over 1000 rice mills across Myanmar are being powered by rice husk small scale biomass gasifiers. After 2001, few rice husk biomass power plant were installed by rural cooperatives/committees for rural electrification. The present investigation focuses to explore the self-sustaining energy service model to provide grid quality power to rural populations without the need of subsidies. The power system model focusing on both power requirements for the productive use and the neighboring villages/rural households at affordable tariff could become the most appropriate solution for the sustainable rural electrification. It is argued that the rice husk biomass power system installed and operated by rice millers is not only the sustainable and affordable option to rural electrification but also the financially viable business model to provide the grid quality power to rural population without grant or subsidy. Furthermore, the modern energy policy objectives-energy security, affordability, and sustainability are also met with the biomass rice husk power plant.